1992
DOI: 10.1203/00006450-199206000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Responses to Acute Maternal Alcohol Intoxication in Immature Fetal Sheep

Abstract: ABSTRACT. Previous studies in mature fetal sheep have and behavioral problems (3). Several of these neurologic abnorshown that alcohol depresses cerebral blood flow (CBF), malities have been produced in animals exposed to alcohol in cerebral O2 consumption (CMR02), and cerebral glucose utero (4). However, the mechanism(s) by which alcohol produces consumption (CMRglu). This effect earlier in gestation brain damage and the vulnerable developmental period (if any) might contribute to the pathogenesis of fetal al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…However, their study was acute and was conducted on exteriorized fetal sheep under general anaesthesia, conditions that could have affected the responses to ethanol. Gleason & Hotchkiss (1992) reported that a single ethanol (1 g kg −1 ) infusion did not alter CBF in 92 day gestation fetal sheep. However, developmental differences in the fetal vascular response to maternal ethanol consumption would be expected since, for example, nitric oxide synthase expression varies not only regionally but also temporally during development (Northington et al 1997).…”
Section: Discussionmentioning
confidence: 95%
“…However, their study was acute and was conducted on exteriorized fetal sheep under general anaesthesia, conditions that could have affected the responses to ethanol. Gleason & Hotchkiss (1992) reported that a single ethanol (1 g kg −1 ) infusion did not alter CBF in 92 day gestation fetal sheep. However, developmental differences in the fetal vascular response to maternal ethanol consumption would be expected since, for example, nitric oxide synthase expression varies not only regionally but also temporally during development (Northington et al 1997).…”
Section: Discussionmentioning
confidence: 95%
“…Although we did not measure cerebral oxygen delivery, it is unlikely to have been globally reduced as neither fetal MAP nor PaO 2 were reduced by EtOH. Previous studies have reported that EtOH infusions in pregnant sheep either do not alter fetal cerebral blood flow (Gleason and Hotchkiss, 1992), or may cause transient reductions (Richardson et al, 1985). Alcohol is known to be vasoactive (Mathew and Wilson, 1991) and it may induce regional differences in blood flow within the fetal brain (Parnell et al, 2007); clearly further studies on the effects of fetal alcohol exposure on cerebral oxygen delivery are required.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that maternal alcohol infusions that create maternal BACs of 246 mg/dl do not reduce fetal PaO 2 or fetal blood pressure (Cudd et al, 1999). However, these findings do not preclude the possibility that even though systemic PaO 2 and circulation pressures were maintained, brain tissue may have been subject to hypoxic conditions perhaps by a selective alteration in cerebral circulation, a hypothesis supported by literature which demonstrates that alcohol can alter cerebral blood flow during the early (Gleason and Hotchkiss, 1992) and late fetal periods (Richardson et al, 1985) and in the adult (Mayhan, 1992).…”
Section: Discussionmentioning
confidence: 73%